Best‐practice forestry management delivers diminishing returns for coral reefs with increased land‐clearing. Issue 12 (22nd September 2020) - Wenger, Amelia S.; Harris, Daniel; Weber, Samuel; Vaghi, Ferguson; Nand, Yashika; Naisilisili, Waisea; Hughes, Alec; Delevaux, Jade; Klein, Carissa J.; Watson, James; Mumby, Peter J.; Jupiter, Stacy D.
Abstract: Protection of coastal ecosystems from deforestation may be the best way to protect coral reefs from sediment runoff. However, given the importance of generating economic activities for coastal livelihoods, the prohibition of development is often not feasible. In light of this, logging codes of practice have been developed to mitigate the impacts of logging on downstream ecosystems. However, no studies have assessed whether managed land‐clearing can occur in tandem with coral reef conservation goals. This study quantifies the impacts of current land use and the risk of potential logging activities on downstream coral reef condition and fisheries using a novel suite of linked land‐sea models, using Kolombangara Island in the Solomon Islands as a case study. Further, we examine the ability of erosion reduction strategies stipulated in logging codes of practice to reduce these impacts as clearing extent increases. We found that with present‐day land use, reductions in live and branching coral cover and increases in turf algae were associated with exposure to sediment runoff from catchments and log ponds. Critically, reductions in fish grazer abundance and biomass were associated with increasing sediment runoff, a functional group that accounts for ~25% of subsistence fishing. At low clearing extents, although best management practices minimize the exposure of coral reefs to increased runoff, it would still result in 32% of the reef experiencing an increase in sediment exposure. If clearing extent increased, best management practices would have no impact, with a staggering 89% of coral reef area at risk compared to logging with no management. Synthesis and applications . Assessing trade‐offs between coastal development and protection of marine resources is a challenge for decision makers globally. Although development activities requiring clearing can be important for livelihoods, our results demonstrate that new logging in intact forest risks downstream resources important for both food and livelihood security. Importantly, our approach allows for spatially explicit recommendations for where terrestrial management might best complement marine management. Finally, given the critical degradation feedback loops that increased sediment runoff can reinforce on coral reefs, minimizing sediment runoff could play an important role in helping coral reefs recover from climate‐related disturbances. Abstract : Assessing trade‐offs between coastal development and protection of marine resources is a challenge for decision makers globally. Although development activities requiring clearing can be important for livelihoods, our results demonstrate that new logging in intact forest risks downstream resources important for both food and livelihood security. Importantly, our approach allows for spatially explicit recommendations for where terrestrial management might best complement marine management. Finally, given the critical degradation feedback loops that increased sediment runoff can reinforce on coral reefs, minimizing sediment runoff could play an important role in helping coral reefs recover from climate‐related disturbances. Editor's Choice